Predictive value of the THRIVE score for outcome in patients with acute basilar artery occlusion treated with thrombectomy - Beilei Chen; Liu Yang; Jing Hang; Shoujiang You; Jun Li; Xiaobo Li; Liangzhu Wang; Li Jiang; Wei Li; Hailong Yu (Brain and Behavior, 2019)
Abstract Background and purpose A higher Totaled Health Risks in Vascular Events (THRIVE) score has been shown to predict poor functional outcome in patients with acute ischemic stroke (AIS) and anterior circulation large vessel occlusions undergoing thrombectomy treatment. We attempted to evaluate the value of the THRIVE score in predicting the outcome of thrombectomy treatment in AIS patients with basilar artery occlusion (BAO). Methods A total of 68 AIS patients with BAO who underwent thrombectomy treatment from May 2014 to August 2018 were included in the present study. Multivariable logistic regression was performed to determine the predictive value of the THRIVE score for poor functional outcome (defined as modified Rankin Scale score ≥ 3), all‐cause mortality, and hemorrhage transformation (HT) at 3 months. Results A total of 42 (61.8%) participants experienced poor functional outcomes, 25 (36.8%) patients died from all causes, and 21 (30.9%) patients had HT during the 3‐month follow‐up. Multivariable logistic regression showed that a higher THRIVE score was significantly associated with poor functional outcome (odds ratio [OR] 5.86, 95% confidence interval [CI], 2.28–14.91, p < .001) as well as all‐cause mortality (OR 2.40, 95% CI, 1.32–4.34, p = .004) but not HT (p = .607). The C‐statistic of the THRIVE score was significantly larger than that of the NIHSS score for predicting poor functional outcome (AUC = 0.913; cutoff > 5; sensitivity, 88.5%; specificity, 83.3%, p = .007) and all‐cause mortality (AUC = 0.768; cutoff > 5; sensitivity, 92.0%; specificity, 65.1%, p = .018). Conclusions A high THRIVE score was independently associated with an increased risk of poor functional outcome and all‐cause mortality in AIS patients with BAO who underwent thrombectomy treatment. Moreover, the THRIVE score appeared to be a better predictor of clinical outcome than the NIHSS score.